Selected Chemical Properties of Soybean Rhizosphere Soil as Influenced by Cropping Systems, Rhizobium Inoculation, and the Supply of Phosphorus and Potassium after Two Consecutive Cropping Seasons - Daniel Nyoki; Patrick A. Ndakidemi (International Journal of Agronomy)
The field experiment was carried out in northern Tanzania to assess the effects of intercropping systems, Rhizobium inoculation, and fertilization with P and K on chemical properties of soybean rhizosphere soil. The experiment was laid out in split-split plot design with 2 × 4 × 7 factorial arrangement replicated thrice. The main plots had two inoculation treatments and the subplots were comprised of four cropping systems which were sole maize, sole soybean, and two intercropping at different soybean spacing (75 × 20 and 75 × 40 cm). The fertilizer levels (kg/ha) control (0 kg/ha); 20 K; 40 K; 26 P; 52 P; 26 P + 20 K; and 52 P + 40 K were assigned to sub-subplots. Statistical analysis was performed using ANOVA. Least Significant Difference was used to compare treatment means at p=0.05 significance level. The results indicated that rhizosphere soil chemical properties such as pH, organic carbon (OC), and macro- and micronutrients (N, P, Ca, Mg, and Na and Fe, Cu, Mn, and Zn, resp.) were significantly increased in the Rhizobium inoculated soybean over the control. The supply of P and K fertilizers significantly increased the rhizosphere content of macronutrients (P, K, Ca, and Mg) and also they altered the pH and EC of the rhizosphere soil relative to control.